2011
DOI: 10.1073/pnas.1107452108
|View full text |Cite
|
Sign up to set email alerts
|

Impaired phosphorylation of Na + -K + -2Cl cotransporter by oxidative stress-responsive kinase-1 deficiency manifests hypotension and Bartter-like syndrome

Abstract: Na + -K + -2Cl − cotransporters (NKCCs), including NKCC1 and renal-specific NKCC2, and the Na + -Cl − cotransporter (NCC) play pivotal roles in the regulation of blood pressure (BP) and renal NaCl reabsorption. Oxidative stress-responsive kinase-1 (OSR1) is a known upstream regulator of N(K)CCs. We generated and analyzed global and kidney tubule-specific (KSP) OSR1 KO mice to elucidate the physiological role of OSR1 in vivo, particularly on BP and kidney function. Although global OSR1 −/− mice were embryonical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
140
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 37 publications
(44 reference statements)
5
140
0
Order By: Relevance
“…Although in sensory neurons the two kinases seem to fulfill a redundant function (12) based on the phenotypes of SPAK and kidney-specific OSR1 knock-out mice, the two kinases in kidney seem to have very distinct roles. Indeed, although the SPAK knock-out mouse reveals a primary role for SPAK in regulating the Na-Cl cotransporter in the distal convoluted tubule (13)(14)(15)(16), the kidney-specific OSR1 knock-out mouse displays a phenotype that is consistent with disruption of NKCC2 function in the TAL (17). An intriguing observation from the SPAK knock-out mouse is that NKCC2 in the TAL is hyperphosphorylated (13,14,16), which would be inconsistent if the kinase was phosphorylating this cotransporter under normal conditions.…”
mentioning
confidence: 89%
“…Although in sensory neurons the two kinases seem to fulfill a redundant function (12) based on the phenotypes of SPAK and kidney-specific OSR1 knock-out mice, the two kinases in kidney seem to have very distinct roles. Indeed, although the SPAK knock-out mouse reveals a primary role for SPAK in regulating the Na-Cl cotransporter in the distal convoluted tubule (13)(14)(15)(16), the kidney-specific OSR1 knock-out mouse displays a phenotype that is consistent with disruption of NKCC2 function in the TAL (17). An intriguing observation from the SPAK knock-out mouse is that NKCC2 in the TAL is hyperphosphorylated (13,14,16), which would be inconsistent if the kinase was phosphorylating this cotransporter under normal conditions.…”
mentioning
confidence: 89%
“…pressure (70,94). Recent studies of C. elegans gck-3 mutants have broadened GCK-VI function to include multiple developmental processes, including epithelial tube morphogenesis and spermatogenesis (37,58).…”
Section: R179 Salt and Water Homeostasis In C Elegansmentioning
confidence: 99%
“…Consistent with the unanticipated highly focused phenotype, phosphorylation of NCC, but not NKCC2, is attenuated in these SPAK knock-out mice. Remarkably, SPAK gene ablation actually leads to an increase in NKCC2 phosphorylation (2), a phenotype that seems to be absent in the catalytically inactive SPAK knock-in mouse (4). Examining a different SPAK null strain, which has been reported to be surprisingly normotensive and have normal levels of aldosterone, McCormick et al (3) suggested that removal of a TAL-specific inhibitory SPAK isoform, KS-SPAK, in the SPAK Ϫ/Ϫ mice would allow OSR1 to hyperphosphorylate NKCC2.…”
mentioning
confidence: 99%
“…Both have been implicated in controlling the activity of NKCC2 and NCC, the co-transporters responsible for salt reabsorption in the thick ascending limb and distal convoluted tubule (1)(2)(3)(4)(5)(6)(7). As the two individual members of the germinal center kinase VI subfamily of STE20 kinases (8), SPAK and OSR1 exhibit a high degree of structural homology, and share similar common domain architectures.…”
mentioning
confidence: 99%
See 1 more Smart Citation